Pole piece coating method

Through multi-layer step-by-step coating and segmented drying, the problems of uneven slurry and low thickness control accuracy in lithium battery electrode coating are solved, the consistency and stability of lithium batteries are improved, and the Productivity.

CN119400808APending Publication Date: 2025-02-07GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411447139.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the existing lithium battery electrode coating process, there are problems such as uneven slurry, low thickness control accuracy, low drying efficiency, and easy bubbles and wrinkles, which affect the performance and quality of lithium batteries.

Method used

Using a multi-layer step-by-step coating method, first coat a thinner first film layer, then coat a thicker second film layer, and perform a brief drying process between each layer, combined with segmented drying, first The first film layer was dried at low temperature and low wind speed, and the second film layer was dried at high temperature and high wind speed.

Benefits of technology

It significantly improves the uniformity and thickness accuracy of coating, reduces coating defects, improves the consistency and stability of lithium batteries, improves drying efficiency, shortens production cycles, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400808A_ABST
    Figure CN119400808A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a pole piece coating method. According to the method, a multi-layer step-by-step coating method is adopted, the thin first film layer is firstly coated, then the thick second film layer is coated, and transient drying treatment is carried out between coating of each layer, so that bubbles and wrinkles are effectively reduced. And meanwhile, sectional type drying is adopted, the first film layer is primarily dried at low temperature and low air speed, then the second film layer is rapidly dried at high temperature and high air speed, and the drying efficiency and quality are improved. According to the coating method, the coating uniformity and the thickness precision can be remarkably improved, the coating defects are reduced, and the consistency and the stability of the lithium battery are improved. In addition, the drying efficiency is improved, the production period is shortened, and energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a pole piece coating method. Background Art

[0002] Battery coating refers to the process of evenly coating electrode materials on a conductive substrate during battery manufacturing to form an electrode film layer to achieve electrochemical reactions and charge transfer between the positive and negative electrodes of the battery. The coating process is to evenly coat the prepared slurry on a conveyor belt and dry it. High-quality coated electrodes have a smooth surface, uniform coating, good adhesion, dryness, no material peeling, no material falling off, no material shortage, no dust accumulation, no scratches, and no bubbles. As the most important process in the pre-process of lithium batteries, the quality of coating directly determines the safety and consistency of lithium batteries.

[0003] At present, the coating method of power lithium battery pole pieces is to use metal foil as the base tape, flatten the base tape by a mechanical device, and then coat the prepared slurry on the base tape according to the predetermined thickness and uniformity by the coating structure, send it into the oven for drying, and then collect it. According to the different coating structures and methods, it can be divided into two types, one is the transfer coating composed of a roller and a scraper, and the other is the extrusion coating composed of an extrusion die. Transfer coating is to transfer the slurry to the base tape by a roller, and then the excess slurry is scraped off by a scraper to achieve thickness and uniformity control. Extrusion coating is to extrude the slurry along the gap on the base tape by a special extrusion die, and control the uniformity and thickness by the extrusion die cavity structure and the gap width. Both methods can achieve continuous coating and automatic control. The existing coating process is prone to problems such as uneven slurry coating, low thickness control accuracy, low drying efficiency, and easy generation of bubbles and wrinkles. These problems seriously affect the performance and quality of lithium batteries. Summary of the invention

[0004] In view of this, the purpose of the present application is to provide a pole piece coating method, which can significantly improve the uniformity and thickness accuracy of the coating, reduce the defects of agglomeration, streaks and scratches in the coating, and thus improve the consistency and stability of the lithium battery.

[0005] In order to solve the above technical problems / achieve the above objectives or at least partially solve the above technical problems / achieve the above objectives, the present application provides a pole piece coating method, comprising:

[0006] S1. preparing an electrode slurry comprising an electrode active material, a conductive agent, a binder, a solvent and a surfactant;

[0007] S2. coating a first film layer on the base tape, wherein the thickness of the first film layer is 25-35% of the expected thickness of the electrode film layer, and then drying at a low temperature and low wind speed;

[0008] S3. Coating a second film layer on the first film layer, wherein the thickness of the second film layer is 65-75% of the expected electrode film layer thickness, and then performing high-temperature and high-wind speed drying to complete the electrode coating.

[0009] Optionally, the surfactant includes 1,3-butanediol and sodium stearate, and the added amount accounts for 0.3-0.6% of the electrode slurry. Further optionally, the mass ratio of the 1,3-butanediol to sodium stearate is 1:1.

[0010] Optionally, the low-temperature and low-wind speed drying comprises:

[0011] Dry at 40-65°C with a wind speed of 1-3m / s for 4-10min.

[0012] Optionally, the high temperature and high wind speed drying comprises:

[0013] Dry at 100-150°C with a wind speed of 5-10m / s for 8-15min.

[0014] Optionally, the coating adopts a slot extrusion coating method; further optionally, the parameters of the slot extrusion coating method include:

[0015] The coating pressure is 0.4-0.7MPa and the flow rate is 8-15mL / s.

[0016] Optionally, S1 includes subjecting the electrode slurry to ultrasonic treatment.

[0017] Optionally, during the coating process, a laser thickness gauge and an image detection system are used to detect the coating thickness and surface quality every 8-15 seconds. When the thickness deviation exceeds ±(4-7) μm or surface defects occur, the coating parameters are adjusted.

[0018] The present application adopts a multi-layer step-by-step coating method, first coating a thinner first film layer, and then coating a thicker second film layer, with a short drying treatment between each coating layer, which effectively reduces the generation of bubbles and wrinkles. At the same time, segmented drying is adopted, first the first film layer is preliminarily dried at low temperature and low wind speed, and then the second film layer is quickly dried at high temperature and high wind speed to improve drying efficiency and quality. The coating method of the present application can significantly improve the uniformity and thickness accuracy of the coating, reduce coating defects, and improve the consistency and stability of lithium batteries. In addition, it also improves drying efficiency, shortens production cycle, and reduces energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.

[0020] Figure 1 The figure shows a schematic diagram of the pole piece structure obtained by the pole piece coating method of the present application;

[0021] Figure 2 The figure shows the surface condition of the electrode film layer after coating of Examples 1 to 4 of the present application; wherein AB represents the results of Examples 1 to 4 respectively;

[0022] Figure 3 Shown are actual pictures of the surface conditions of the electrode film layers after coating of Comparative Examples 1 to 4; wherein, AB represent the results of Comparative Examples 1 to 4, respectively. DETAILED DESCRIPTION

[0023] The present application discloses a pole piece coating method, and those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0024] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.

[0025] In view of the fact that both conventional transfer coating and extrusion coating have poor drying efficiency, uneven coating and coating defects, the present application provides a pole piece coating method, including:

[0026] S1. preparing an electrode slurry comprising an electrode active material, a conductive agent, a binder, a solvent and a surfactant;

[0027] S2. coating a first film layer on the base tape, wherein the thickness of the first film layer is 25-35% of the expected thickness of the electrode film layer, and then drying at a low temperature and low wind speed;

[0028] S3. Coating a second film layer on the first film layer, wherein the thickness of the second film layer is 65-75% of the expected electrode film layer thickness, and then performing high-temperature and high-wind speed drying to complete the electrode coating.

[0029] In certain embodiments of the present application, the surfactant includes 1,3-butanediol and sodium stearate, and the added amount accounts for 0.3-0.6% of the electrode slurry. 1,3-Butanediol, ethylene carbonate, and propylene carbonate are often added to the slurry to prevent the cracking of the pole piece, but these substances have limited improvement on the interface defects that appear during the coating process, such as agglomeration, scratches, and streaks. Therefore, the present application adds sodium stearate on this basis to further eliminate such coating interface defects. Preferably, the mass ratio of 1,3-butanediol and sodium stearate is 1:1. In some other embodiments of the present application, S1 also performs ultrasonic dispersion treatment on the electrode slurry to remove the agglomerated particles therein and improve the dispersibility of the slurry. The ultrasonic treatment time can be selected to be 20-35 minutes.

[0030] In order to effectively reduce coating defects, such as wrinkles and bubbles, the present application adopts a multi-layer distribution coating method. In order to achieve a better coating effect, the present application controls the thickness of the first film layer to be 25-35% of the expected electrode film thickness, such as 25%, 30% and 35%; at the same time, in order to cooperate with this multi-layer distribution coating method, the present application performs low-temperature and low-wind speed drying after the thinner first film layer is coated, specifically including drying at 40-65°C and 1-3m / s wind speed for 4-10min. In this link, the first film layer can be preliminarily dried to ensure that it has a certain degree of solidification but will not be completely dried, so that it can be completely integrated with the subsequent thicker second film layer to form an electrode film layer, while reducing the drying time of the second film layer; in some embodiments of the present application, the temperature of the low-temperature and low-wind speed drying can be selected as 40°C, 50°C, 55°C or 60°C, the wind speed can be selected as 1.5m / s, 2m / s, 2.5m / s or 3m / s, and the drying time can be selected as 4min, 5min, 6min or 7min.

[0031] In certain embodiments of the present application, the thickness of the thicker second film layer accounts for 65-75% of the expected electrode film layer thickness, that is, the coating of the remaining electrode film layer thickness is completed after the first film layer is coated, and the thicker second film layer needs to be dried at high temperature and high wind speed, specifically including: drying at 100-150°C and a wind speed of 5-10m / s for 8-15min. In certain embodiments of the present application, the temperature of the high temperature and high wind speed drying can be selected as 110°C, 120°C, 130°C or 140°C, the wind speed can be selected as 7m / s, 8m / s, 9m / s or 10m / s, and the drying time can be selected as 8min, 10min, 12min or 15min.

[0032] In certain embodiments of the present application, the coating adopts a slit extrusion coating method; wherein the parameters of the slit extrusion coating method include: coating pressure of 0.4-0.7MPa, flow rate of 8-15mL / s. Compared with transfer coating, the advantages of the extrusion coating system are that the electrode is very uniform and high in precision after coating, the coating edge is flat, and the closed operating system is not affected by foreign matter.

[0033] On the basis of the layered coating and drying scheme in the present application, by combining ultrasonic dispersion treatment of the slurry and the addition of specific surfactants, as well as controlling appropriate parameters such as pressure and flow rate of slit extrusion coating, better coating effects can be achieved; in addition, taking into account the influence of objective mechanical equipment, environment, and materials, in order to further ensure the coating effect, the present application also includes the use of a laser thickness gauge and an image detection system to detect the coating thickness and surface quality every 8-15 seconds during the coating process. When the thickness deviation exceeds ±(4-7) μm or surface defects occur, the coating parameters are adjusted in time to adapt to the changed mechanical equipment and environment.

[0034] In certain embodiments of the present application, the electrode slurry is a negative electrode slurry, including a negative electrode active material, a conductive agent, a binder, 1,3-butanediol, sodium stearate and a solvent; wherein the negative electrode active material can be graphite, the conductive agent can be conductive carbon black, the binder can be styrene-butadiene rubber, and the solvent can be deionized water. The mass percentages of the negative electrode active material, the conductive agent and the binder can be selected according to the conventional battery dosage, for example, 95% of the negative electrode active material, 2% of the binder, 2.5% of the conductive agent, 0.25% of 1,3-butanediol, and 0.25% of sodium stearate. The viscosity of the slurry is generally between 3000 and 8000 Pa·s, and the actual discharge viscosity can be adjusted according to the actual coating equipment.

[0035] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.

[0036] The following is a further description of a pole piece coating method provided in this application.

[0037] Embodiment 1:

[0038] The negative electrode slurry was prepared by mixing the active material, conductive agent, binder and solvent according to the recipe, and performing ultrasonic dispersion treatment for 30 minutes, and adding 0.5% 1,3-butanediol and sodium stearate (1:1).

[0039] A slit extrusion coating head was used to control the coating pressure to 0.5 MPa and the flow rate to 10 mL / s for the first layer coating with a thickness of 50 μm.

[0040] Preliminary drying was carried out at 50°C and a wind speed of 2m / s for 5 minutes, and then a second layer was coated with a thickness of 150μm.

[0041] The coating was dried quickly for 10 minutes at 120°C and wind speed 8m / s. Figure 2 -A, Figure 2 -A shows that there are no interface defects on the surface of the electrode film layer after coating by the coating method of the present application, and the entire film layer is flat and uniform.

[0042] Embodiment 2:

[0043] The negative electrode slurry was prepared by mixing the active material, the conductive agent, the binder and the solvent according to the recipe, and performing ultrasonic dispersion treatment for 20 minutes, and adding 0.3% of a surfactant.

[0044] A slit extrusion coating head was used to control the coating pressure to 0.4 MPa and the flow rate to 8 mL / s for the first layer coating with a thickness of 40 μm.

[0045] Preliminary drying was carried out at 45°C and a wind speed of 1.5 m / s for 4 minutes, and then a second layer was coated with a thickness of 160 μm.

[0046] The coating was dried quickly for 8 minutes at 110℃ and wind speed 7m / s. Figure 2 -B, Figure 2 -B also shows that there are no interface defects on the surface of the electrode film layer after coating by the coating method of the present application, and the entire film layer is flat and uniform.

[0047] Embodiment 3:

[0048] The negative electrode slurry was prepared by mixing the active material, the conductive agent, the binder and the solvent according to the recipe, and performing ultrasonic dispersion treatment for 25 minutes, and adding 0.4% of a surfactant.

[0049] A slit extrusion coating head was used to control the coating pressure to 0.6 MPa and the flow rate to 12 mL / s for the first layer coating with a thickness of 60 μm.

[0050] Preliminary drying was carried out at 55°C and a wind speed of 2.5 m / s for 6 minutes, and then a second layer was coated with a thickness of 140 μm.

[0051] The coating was dried quickly for 12 minutes at 130°C and wind speed 9m / s. Figure 2 -C, Figure 2 -C also shows that there are no interface defects on the surface of the electrode film layer after coating by the coating method of the present application, and the entire film layer is flat and uniform.

[0052] Embodiment 4:

[0053] To prepare the negative electrode slurry, the active material, the conductive agent, the binder and the solvent were mixed according to the recipe, and ultrasonic dispersion was performed for 35 minutes, and 0.6% of the surfactant was added.

[0054] A slit extrusion coating head was used to control the coating pressure to 0.7 MPa and the flow rate to 15 mL / s for the first layer coating with a thickness of 70 μm.

[0055] Preliminary drying was carried out at 60°C and a wind speed of 3 m / s for 7 minutes, and then a second layer was coated with a thickness of 130 μm.

[0056] The coating was dried quickly for 15 minutes at 140°C and a wind speed of 10 m / s. Figure 2 -D, Figure 2 -D also shows that there are no interface defects on the surface of the electrode film layer after coating by the coating method of the present application, and the entire film layer is flat and uniform.

[0057] Comparative Example 1:

[0058] The method of Example 1 is referred to, except that no stratification is performed, and a 200 μm electrode film layer is directly coated at one time, and then the high temperature and high wind speed in Example 1 are used for drying. It takes about 15 minutes in total to reach the same drying level as in Example 1. The surface condition of the film layer is shown in FIG. Figure 3 -A, the box in the figure shows the interface defect phenomenon of agglomeration.

[0059] Comparative Example 2:

[0060] Referring to the method of Example 1, the difference is that the first film layer and the second film layer are exchanged in order, and the drying method is still to first dry at low temperature and low wind speed and then at high temperature and high wind speed. It takes about 17 minutes in total to reach the same drying level as Example 1. The surface condition of the film layer is shown in FIG. Figure 3-B, there is an interface defect phenomenon with abnormal vertical stripes at the arrow position in the figure.

[0061] Comparative Example 3:

[0062] According to the method of Example 1, only 1,3-butanediol was used as the surfactant. It took about 16 minutes to reach the same drying level as Example 1. The surface condition of the film layer was shown in FIG. Figure 3 -C, there is an interface defect phenomenon with a dark mark at the position of the arrow in the figure.

[0063] Comparative Example 4:

[0064] Referring to the method of Example 1, the high temperature and high wind speed drying parameters were used for drying the first film layer, and the low temperature and low wind speed drying parameters were used for drying the second film layer. It took a total of 25 minutes to reach the same drying level as in Example 1. The surface condition of the film layer is shown in FIG. Figure 3 -D, there is an interface defect phenomenon of abnormal scratches at the position of the arrow in the figure.

[0065] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A pole piece coating method, characterized in that: include: S1. preparing an electrode slurry comprising an electrode active material, a conductive agent, a binder, a solvent and a surfactant; S2. coating a first film layer on the base tape, wherein the thickness of the first film layer is 25-35% of the expected thickness of the electrode film layer, and then drying at a low temperature and low wind speed; S3. Coating a second film layer on the first film layer, wherein the thickness of the second film layer is 65-75% of the expected electrode film layer thickness, and then performing high-temperature and high-wind speed drying to complete the electrode coating.

2. The electrode coating method according to claim 1, characterized in that: The surfactant includes 1,3-butanediol and sodium stearate, and the added amount accounts for 0.3-0.6% of the electrode slurry.

3. The pole piece coating method according to claim 2, characterized in that: The mass ratio of the 1,3-butanediol to sodium stearate is 1:

1.

4. The electrode coating method according to claim 1, characterized in that: The low temperature and low wind speed drying comprises: Dry at 40-65°C with a wind speed of 1-3m / s for 4-10min.

5. The coating method according to claim 1, characterized in that: The high temperature and high wind speed drying comprises: Dry at 100-150°C with a wind speed of 5-10m / s for 8-15min.

6. The electrode coating method according to claim 1, characterized in that: The coating adopts a slot extrusion coating method.

7. The pole piece coating method according to claim 6, characterized in that: The slot die coating method parameters include: The coating pressure is 0.4-0.7MPa and the flow rate is 8-15mL / s.

8. The electrode coating method according to claim 1, characterized in that: S1 includes subjecting the electrode slurry to ultrasonic treatment.

9. The pole piece coating method according to any one of claims 1 to 8, characterized in that: During the coating process, a laser thickness gauge and an image detection system are used to detect coating thickness and surface quality every 8-15 seconds. When the thickness deviation exceeds ±(4-7)μm or surface defects occur, the coating parameters are adjusted.

Citation Information

Cited By

  • Precise coating forming method for lithium ion battery pole piece

    CN120895601A